Investigation of Ventilator Associated Pneumoniae in Intensive Care Patients - Hakan Tağrıkulu; Dilek Memiş; Nesrin Turan (Galenos Yayinevi, 2016)
Objective: Mechanical ventilator associated pneumonia is a serious infection occurred frequently in intensive care units and associated with high mortality. In this study we aimed to investigate the incidence of ventilator associated pneumonia, the duration of mechanical ventilation, length of intensive care unit stay, complication occurrence and mortality rates on patients undergoing mechanical ventilation for more than 48 hours. Material and Method: Two hundred twenty patients were included in the study. Demographic data at the time of the admission to intensive care unit (age, sex, height, weight and body mass index), intensive care admission diagnosis and systemic diseases were all recorded. The clinical pulmonary infection score was used for ventilator associated pneumonia diagnosis. Antibiotic usage, duration of stay in intensive care unit, duration of mechanical ventilation stay and mortality were all recorded. Results: Ventilator-associated pneumonia was detected in 51.36% (n=113) of the 220 patients. Clinical pulmonary infection score was found as 8.04±1.03 in patients with ventilator-associated pneumonia and 1.75±1.88 in non- ventilatorassociated pneumonia patients (p=0.001). Higher age was detected in ventilator-associated pneumonia group (58±12.79 years and 51.37±15.87 years, p=0.001). Also hypertension and diabetes mellitus were observed more frequently (p=0.001). Development of enteral nutrition in patients with ventilator-associated pneumonia were significantly higher than those of parenterally fed patients (enteral: by 36.4% and 25.5% p=0.006; parenteral: 25% and 19.1%, p=0.042). The length of stay in intensive care unit (12.38±5.81 and 10.79±5.91 days, p=0.045), duration of mechanical ventilation (9.67±4.84 days and 6.7±3.87 days, p=0.001) and mortality rates (24.5% and 15.5% p=0.019) were significantly higher in the ventilator-associated pneumonia group. Conclusion: Ventilator-associated pneumonia increases the duration of mechanical ventilation, length of Intensive Care Unit stay, antibiotic usage and mortality.